2016
DOI: 10.3762/bjnano.7.47
|View full text |Cite
|
Sign up to set email alerts
|

First-principles study of the structure of water layers on flat and stepped Pb electrodes

Abstract: SummaryOn the basis of perodic density functional theory (DFT) calculations, we have addressed the geometric structures and electronic properties of water layers on flat and stepped Pb surfaces. In contrast to late d-band metals, on Pb(111) the energy minimum structure does not correspond to an ice-like hexagonal arrangement at a coverage of 2/3, but rather to a distorted structure at a coverage of 1 due to the larger lattice constant of Pb. At stepped Pb surfaces, the water layers are pinned at the step edge … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
26
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
2
1
1

Relationship

3
6

Authors

Journals

citations
Cited by 24 publications
(28 citation statements)
references
References 61 publications
1
26
0
1
Order By: Relevance
“…Ab initio molecular dynamics (AIMD) simulations were performed to account for thermal fluctuations in ordering of surficial water at Ni (oxy)hydroxides (001). This computational study expands the scope of similar studies on water/transition metal interfaces [29,39,40,41,42,43,44,45] towards water/oxides surfaces.…”
Section: Introductionsupporting
confidence: 58%
See 1 more Smart Citation
“…Ab initio molecular dynamics (AIMD) simulations were performed to account for thermal fluctuations in ordering of surficial water at Ni (oxy)hydroxides (001). This computational study expands the scope of similar studies on water/transition metal interfaces [29,39,40,41,42,43,44,45] towards water/oxides surfaces.…”
Section: Introductionsupporting
confidence: 58%
“…Among various examined orientations shown in Table 1, it was found that on β-NiOOH 25/75 (001) a water monomer binds via its oxygen atom to OH ad with d H2O-OH = 2.70 Å, as can be seen in In order to separate water-NiO x from water-water interactions, we performed an energy calculation for an isolated hexagonal water layer with all water molecules fixed in positions as in the configuration of the water layer when adsorbed on β-Ni(OH) 2 (001) or β-NiOOH 75/25 (001). The strength of water-water interactions can be calculated as [41],…”
Section: Resultsmentioning
confidence: 99%
“…Single water molecules adsorb on close-packed metal surfaces typically through their oxygen atom at a top position in a flat configuration with the hydrogen atoms almost at the same height as the oxygen atom [17,44]. This is also the case for isolated water molecules at a coverage of 1 3 adsorbed on PtRu/Pt(111) surface alloys, as illustrated for a Pt 2 Ru 1 /Pt(111) surface alloy in figure 1.…”
Section: Resultsmentioning
confidence: 78%
“…Pemodelan dari aspek interaksi antara permukaan elektroda dan sisi dinamika molecular molekul H2O yang bertabrakan atau bersentuhan dengan permukaan elektroda sehingga proses splitting bisa dijelaskan. Permukaan elektroda menjadi kajian yang menarik diteliti seperti dilaporkan Xu et al (2017) tentang factor roughness pada permukaan padatan berpori terhadap evolusi gas yang dihasilkan (11)(12)(13)(14). Dalam paper ini ditelaah kemungkinan pola interaksi molecular H2O dan permukaan padatan elektroda melalui pemodelan.…”
Section: Pendahuluanunclassified